Solvatochromic covalent organic frameworks - Laura Ascherl (Nature Portfolio, 2018)
Covalent organic frameworks (COFs) find increasing application as sensor material, but fast switching solvatochromism was not realized. Here the authors demonstrate that combination of electron-rich and -deficient building blocks leads to COFs which fast and reversibly change of their electronic structure depending on the surrounding atmosphere.